ANALISIS BREAK EVEN POINT PADA USAHA DAGANG AZ-ZAHRA DI JALAN GERILYA SAMARINDA - Nor, Isnaniah; Zaini, M.; Salim, Umar Hi (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This study aims to calculate the Break Even Point (BEP) in the form of units and rupiah of egg-type products and analyze the development of egg sales in the Az-Zahra trading business in 2020 and 2021. This research uses a descriptive method with a quantitative strategy. Field research data collection techniques are obtained through interviews and observations and are supported by literature research data, namely information through books, previous research writings, and literature books related to research. The data obtained are then analyzed using the calculation of Break Even Point (BEP) in the form of units and rupiah and Break Even Point (BEP) in Chart. The results of the research in the Break Even Point (BEP) analysis of the Az-Zahra trading business are distinguishing fixed costs, variable costs, and semivariable costs, describing the purchase price, selling price, and sales volume of units and rupiah. The data obtained further conducted a research analysis with the separation of fixed costs and variable costs on six types of eggs with a percentage of small purebred eggs 19%, large purebred eggs 50%, jumbo purebred eggs 15%, duck eggs 10%, salted eggs 5%, and quail eggs 1% of the total egg sales, calculated variable costs per unit, contribution margin and profit, contribution margin per unit, and calculate Break Even Point (BEP) in the form of units and rupiah. With this, Az-Zahra's trading business has reached breakeven and has gained profits so that it can analyze the development of egg sales in unit form has decreased by 1.3% while egg sales have increased by 1.2%.